TRANSLATING METAPHORS IN LITERARY TEXTS: STRATEGIES AND CHALLENGES - Sodiqova Nargiza Baxodir qizi (International Journal of Literature and Language Studies, 2026)
Metaphor is one of the most important expressive devices in literary writings, acting not only as a stylistic tool but also as a means of expressing cultural values, emotions, and philosophical meaning. Metaphor translation is thought to be a challenging process since metaphorical expressions are frequently deeply embedded in the source language's linguistic, cognitive, and cultural systems. The goal of this article is to look at the translation procedures used to convey metaphors in literary texts and to discover the elements that impact translators' decisions. Drawing on the theoretical perspectives of scholars in metaphor and translation studies, including cognitive and cultural approaches, the paper discusses strategies such as reproducing the same metaphor, replacing it with an equivalent target-language metaphor, translating it through simile, rendering it through paraphrase or equivalence, and omitting it entirely. The findings show that no single universal technique can accurately translate all metaphorical terms in literary discourse. Rather, the semantic qualities of the metaphor, the degree of cultural distinctiveness, and the level of conceptual compatibility between the source and destination languages all influence the technique used. The study emphasises the necessity of taking into account both cognitive and cultural dimensions when translating metaphors, and it shows that good translation necessitates balancing semantic correctness with the preservation of aesthetic and cultural connotations. The study helps to deepen our theoretical understanding of metaphor translation and provides a valuable framework for literary translators and academics.